2010
DOI: 10.1590/s1676-06032010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Composição da ictiofauna em função da fisiografia de um riacho costeiro de Floresta Atlântica - Brasil

Abstract: Abstract:In spite of the impacts that tropical streams are submitted, they still present a great fish diversity. The knowledge of the fish structure and composition is an important attempt in order to stabilish evaluation parameters that can favour conservation of these environments. The icthyofaunal composition related to physiographic features of coastal streams of south Brazil is an important contribution to the interpretation of these ecosystem dynamics. We perform fish collections in five sampling sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
0
8
0
3
Order By: Relevance
“…The Atlantic Rain Forest has a rich ichthyofauna, estimated about 270 species, belonging to 89 genera and 21 families (Abilhoa et al 2011;Miranda 2012). However, there are several doubts on species descriptions and on the ecological processes such as heavy water turmoil and vegetation influences on fish assemblages (Guimarães et al 2010). Despite the high biodiversity in the Atlantic Rain Forest, anthropogenic activities have jeopardized this system and there are few studies on streams fish composition and structure (Myers et al 2000;Miranda 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Atlantic Rain Forest has a rich ichthyofauna, estimated about 270 species, belonging to 89 genera and 21 families (Abilhoa et al 2011;Miranda 2012). However, there are several doubts on species descriptions and on the ecological processes such as heavy water turmoil and vegetation influences on fish assemblages (Guimarães et al 2010). Despite the high biodiversity in the Atlantic Rain Forest, anthropogenic activities have jeopardized this system and there are few studies on streams fish composition and structure (Myers et al 2000;Miranda 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The family Characidae was predominant ( Figure 5), mainly due to the abundance of Astyanax ribeirae, Mimagoniates microlepis, and Hollandichthys multifasciatus. The freshwater fish fauna in the sampled streams in JIES is similar to other Brazilian coastal basins, with the predominance of Characiformes and/or Siluriformes (Sabino and Castro 1990;Mazzoni and Lobón-Cerviá 2000;Esteves and Lobón-Cerviá 2001;Uieda and Uieda 2001;Gerhard et al 2004;Serra et al 2007;Ferreira and Petrere Jr. 2009;Guimarães et al 2010;Mattox and Iglesias 2010), and confirms with what is expected in freshwater environments included in the studied region (Lévêque et al 2008). The representation of the Characidae species was also expected, since this family is one of the most species-rich in the Neotropical region (Reis et al 2003).…”
Section: Resultsmentioning
confidence: 51%
“…In addition, the occurrence of marine-estuarine species in coastal streams decreases as the distance from the estuary increases (Leung and Camargo 2005). Nevertheless, A. tajasica was found in distant reaches with little or no marine influence in two streams at JIES, as recorded by Uieda and Uieda (2001), Sabino and Silva (2004), and Guimarães et al (2010) in other Brazilian coastal streams. …”
Section: Resultsmentioning
confidence: 55%
“…Based on the literature, between 20 and 50 fish species are estimated to occur in coastal Atlantic streams of Paraná state (Fogaça et al 2003, Barreto and Aranha 2005, Abilhoa and Bastos 2009, Guimarães et al 2010. Channels located on steep slopes of the Serra do Mar mountains and geographical isolation due the subdivision of eastern Atlantic basin in several sub basins, have conferred to fish smaller sizes and higher degree of endemism (Vari andMalabarba 1998, Menezes et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ancistrus multispinnis inhabits moderate to fast currents dwelling on boulders and cobbles (Barreto and Aranha 2005) and presents larger ventral sucker mouth than other loricariids, which allows it to adhere to the substratum (Breda et al 2005). A congeneric of R. frenatus, Rhamdioglanis transfaciatus Miranda Ribeiro, 1908 with (Guimarães et al 2010), indicating the capacities of these species of swimming among boulders and cobbles. The DCA and statistical tests showed that fish community structure differed only between upper and mouth reaches.…”
Section: Discussionmentioning
confidence: 99%